Pengaruh Range Of Motion (Rom) Pasif Terhadap Perubahan Saturasi Oksigen Pada Pasien Stroke Non Hemoragik - Ni Made Dwi Yunica Astriani; Ni Ketut Putri MarthaSari; Putu Indah Sintya Dewi (UNIVERSITAS SARI MUTIARA INDONESIA, 2022)
Non hemorrhagic stroke is blocked by a blood clot or narrowing of an artery that leads to the brain, possibly also impaired oxygen transfer, resulting in decreased cerebral perfusion. When ROM was done exercise, it can show changes in oxygen saturation. The Purpose of this research to know influence of passive ROM towards changes of oxygen saturation in non hemorrhagic stroke patients in the Sandat Room of RSUD Buleleng. The research design was pre-experiment with one group pre-post test design with 22 respondents selected by using purposive sampling technique with inclusion criteria and sample exclusion. Data collection was done through oxygen saturation change observation sheet. This research used parametric with paired dependet t-test with significant level p = 0,05. The result shows that oxygen saturation change prior to Range Of Motion (ROM) was given by passive oxygen saturation value 90,64% and after passive ROM treatment of oxygen saturation change to 96,09%. Parametric test result using paired dependent t-test obtained p= value pre and post (0,000) p value (0,05), meaning H0 rejected and Ha accepted. So can be conclude that there is influence of passive Range Of Motion (ROM) towards changes of oxygen saturation in non hemorrhagic stroke patients in the Sandat Room of RSUD Buleleng.